PENGARUH KREATIVITAS, MODAL USAHA, DIVERSIFIKASI PRODUK DAN KEBIJAKAN PEMERINTAH TERHADAP KEBERLANJUTAN BISNIS UMKM (STUDI PADA UMKM BIDANG PERDAGANGAN DI KELURAHAN IRINGMULYO KOTA METRO) - Cika Irlia Azzahra; Suyanto Suyanto; Elmira Febri Darmayanti (Jurnal Akuntansi AKTIVA, 2021)
This study aimed to examine the influence of creativity, business capital, product diversification and government policies on business sustainability in the Trade Sector UMKM in Iringmulyo Village, Metro City. The sampling method used was convenience sampling, until a total sample of 86 business actors was obtained. This study used a quantitative approach. The data used are primary data from the results of distributing questionnaires. The data were then processed with IBM Statistics SPSS 24. The results of this study indicated that partially creativity had an effect on business sustainability, business capital had no effect on business sustainability, product diversification had an effect on business sustainability, government policies affected business sustainability as well as simultaneously creativity, capital. business, product diversification and government policies affected business sustainability.Key words: creativity; business Capital; product diversification; government policy; UMKM business continuity